Designing of a Receiver Antenna on the RFID Reader for Motor Vehicle Parking Application at Campus UNIKOM - Cisko Nurdiyanto (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
Technology park in a building already providing services that are so practical by utilizing Radio Frequency Identification (RFID) as a tool to determine the identity of the users of the service park. RFID is one technology that is so fast identification of development. One component is the RFID reader or reader. Reader is one of the main parts that determine the performance of an RFID system that required a good antenna to improve its performance. In this thesis, a small loop antenna which can work on RFID applications have been designed, fabricated, and tested. From the specifications desired for impedance bandwidth of 5-10 KHz for return loss <-14 dB. Gain achievements on the specifications obtained by 1 to 1.5 dB at a resonant frequency of 125 KHz. In the measurement results obtained impedance bandwidth of 8 KHz to return loss <14 dB with a performance gain of -35.61 with cable loss value of -55dBm. The resulting radiation pattern made of small loop antenna is omnidirectional. Antenna design results can be applied to the environment of the campus parking system that can read the original card / tag Â± 2 cm, with a reading distance of an antenna design that can be generated to achieve Â± 6.9 cm.